2015
DOI: 10.1097/coc.0b013e318287bd7f
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume Change With Stereotactic Body Radiotherapy (SBRT) for Early-stage Lung Cancer

Abstract: Significant decrease in GTV volume based on daily CBCT was demonstrated during SBRT treatment. Adaptive SBRT has the potential to minimize integral dose to the surrounding normal tissues without compromising GTV coverage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…These data strongly support the idea that tumor size is a key predictor of outcome in NSCLC patients treated with SBRT 13 . Bhatt et al 32 observed that T-stage was associated with tumor shrinkage during SBRT treatment, with T1 tumors showing greater decrease than T2 tumors. These data imply that patients with larger tumors might benefit from dose escalation (if normal tissue constraints allow).…”
Section: Discussionmentioning
confidence: 99%
“…These data strongly support the idea that tumor size is a key predictor of outcome in NSCLC patients treated with SBRT 13 . Bhatt et al 32 observed that T-stage was associated with tumor shrinkage during SBRT treatment, with T1 tumors showing greater decrease than T2 tumors. These data imply that patients with larger tumors might benefit from dose escalation (if normal tissue constraints allow).…”
Section: Discussionmentioning
confidence: 99%
“…using dose fractionation similar to our study also concluded that most patients experience significant volume reduction after three fractions of treatment. The median OTT for their patients was 15 days …”
Section: Discussionmentioning
confidence: 99%
“…Chest wall toxicity was significantly related to dose-volume parameters 9,10) and in our study, V30 Gy and V32 Gy of the chest wall were significantly reduced in the adaptive plan. Bhatt et al 14) reported that the doses of the chest wall and left ventricle were reduced in adaptive plans compared with initial plans. And, in our study, V20 Gy, D1500 cc, and D1000 cc of the lung, which are related to lung toxicity, were also significantly decreased in the adaptive plan.…”
Section: Discussionmentioning
confidence: 99%
“…12,13) TVC has also been reported even in SBRT despite its short overall treatment time. [14][15][16][17][18] …”
Section: Introductionmentioning
confidence: 99%